UMPSA receives 2 electric vehicles (EV) contributed by Fieldman EV Sdn. Bhd. - Wallid Wahidi, Hamzah (UMPSA, 2025)
PEKAN, 4 October 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received two Changan EADO 460 electric vehicles from Fieldman EV Sdn. Bhd., which will be used for research and teaching purposes in the field of EV technology.